Rancang Bangun Sistem E-commerce Clothing Store dan Modul Custom Design Lab Terintegrasi - paulus lucky tirma irawan; David Rozando (SMATIKA JURNAL, 2020)
The current ease of internet access and convenience in developing website E-commerce is a great alternative for business through The internet. Online clothing stores are one type of E-commerce business that has sprung up in the internet world today. The application of E-commerce in this business can handle the trading process which consists of the order, purchase, payment, and shipping process. Order customization of ordered goods is also one of the added values ​​that can be offered to prospective customers. The existence of a module called the Custom Design Lab can be a solution to this condition. This module in its implementation will be integrated with the existing E-commerce system so that the existing trading process also applies to the preorder system. The development of this E-commerce website uses the PyroCMS framework as a basic application by configuring several modules. The main focus of this research is to produce an E-commerce site that has represented the online business process in general and also has a Custom Design Lab feature for product order customization.